Pengaruh Karakteristik Dewan dan Struktur Kepemilikan Terhadap Kinerja Keuangan Perbankan di Indonesia - Adhi Nugroho; Dita Evelyn Elintra Kloko; Henny Setyo Lestari; Farah Margaretha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
To analyze the effect of board independence, board size, board meetings, managerial ownership, foreign ownership and control variables, namely firm size and firm age on financial performance (Tobin's Q). This research includes quantitative research. The sample in this study were 38 banks in Indonesia with 190 observations in 5 years (2019 - 2023). The data used is secondary data and the data is obtained from companies that publish financial reports and annual reports. The sample withdrawal technique in this study is based on purposive sampling method with certain criteria. Panel data regression analysis was used in this study with the Eviews 12 software analysis tool. The results of this study are Board independence has an effect on financial. Board size has no effect on financial performance as expressed by Tobin's Q. Board meetings have an effect on financial performance. Managerial ownership has no effect on financial performance. Foreign ownership has no effect on financial performance. Firm size affects board characteristics and ownership on financial performance. Firm age does not affect board characteristics and ownership on financial performance.